Influence of Crushed Corn Cob Mass Percentage on the Compression Breaking Strength of Composites with Hybrid Matrix Based on Dammar Resin - Cosmin Mihai Miritoiu (BioResources)
This study investigated the effect of crushed corn cob reinforcement on the compressive strength of composite materials with a hybrid matrix based on dammar (60%) and a synthetic epoxy (Resoltech 1050 with 1058s hardener). While previous research has explored mechanical and chemical properties of such composites, as well as the role of dammar resin, the specific impact of crushed corn cob on compressive strength had not yet been addressed. Materials with reinforcement mass fractions between 50% and 67% were fabricated, each with 15 samples. Power Analysis confirmed the sample size was statistically valid. A null hypothesis—stating that crushed corn cob has no significant influence on compressive strength—was tested and rejected (p < 0.05) using one-way ANOVA. Welch ANOVA confirmed the result (Fw > 2.49), and Kolmogorov-Smirnov tests showed data normality (p > 0.05). Post hoc ANOVA with Bonferroni correction confirmed significant differences between groups. The key finding was that beyond 66% crushed corn cob content, the materials lose engineering relevance due to inadequate compressive strength.